Penerapan Prinsip-Prinsip Perdagangan Internasional (Word Trade Organization) dalam Tinjauan Maqashid Syari’ah - Salman Nashih Amiin; Wirdyaningsih (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The World Trade Organization (WTO) is an international trade organization that regulates international trade activities. The WTO has principles that are firmly held in regulating international trade activities. One of the WTO principles that underlies other principles is non-discrimination, which means equal treatment and does not differentiate between member countries. Agreements with the principle of non-discrimination that must be implemented by every WTO member without exception do not necessarily provide justice to every member because not all members have the same conditions, such as developed countries, developing countries and poor countries. Indonesia, which is a member of the WTO and the majority of Indonesian people who are Muslim, is automatically bound and obliged to implement WTO provisions and Islamic law. The problem studied is the suitability of the application of WTO principles in Islam according to the Maqashid Syar'ah review. The research method used is the doctrinal research method. This research is a literature review (liberary research) sourced from scientific works and WTO principles. The results of this study indicate that there are several applications of WTO principles that are less appropriate in the study of maqashid sharia, namely the principles of Most Favored Nation (MFN) and Reciprocity, but there are several WTO principles that are appropriate to the study of maqashid sharia, namely the principles of National Treatment, Free Trade, Fair Competition, Special and Differential Treatment and Transparency. Keywords: Maqashid syari’ah; Principle of Trade; World Trade Organization